Court of Reflections and Arch of Triumph, California World's Fair on San Francisco Bay (Stanley A. Plitz Company)
In the tranquil Court of Reflections are two large rectangular pools, reflecting the soft coral walls with trailing vines from the parapets. The magnificent Arch of Triumph brilliantly lighted and mirrored in the pools is an awe inspiring sight. Thru the arch can be seen the statue of the Rainbow Girl.